2017
DOI: 10.3892/mmr.2017.6425
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 13q deletion syndrome involving 13q31-qter: A case report

Abstract: Partial deletions on the long arm of chromosome 13 lead to a number of different phenotypes depending on the size and position of the deleted region. The present study investigated 2 patients with 13q terminal (13qter) deletion syndrome, which manifested as anal atresia with rectoperineal fistula, complex type congenital heart disease, esophageal hiatus hernia with gastroesophageal reflux, facial anomalies and developmental and mental retardation. Array comparative genomic hybridization identified 2 regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…Our male patients 2 and 3 have urogenital abnormalities, while the male patient 1, with a deletion that involves only part of the 13q34 band, has no urogenital abnormality, suggesting that the region responsible for the abnormality is within a 7.3-Mb region between positions 104.2 and 111.5 Mb in 13q33.1q34. Located in 13q33.3, the EFNB2 gene has been suggested as a candidate to play a role in male urogenital abnormalities in several studies [Dravis et al, 2004;Garcia et al, 2006;Walczak-Sztulpa et al, 2008;Kirchhoff et al, 2009;Andresen et al, 2010;Wang et al, 2017]. In fact, EFNB2 haploinsufficiency may provide a causative explanation for the observed urogenital abnormalities in our 13q deletion male patients 2 and 3.…”
Section: Urogenital Abnormalitiesmentioning
confidence: 53%
See 2 more Smart Citations
“…Our male patients 2 and 3 have urogenital abnormalities, while the male patient 1, with a deletion that involves only part of the 13q34 band, has no urogenital abnormality, suggesting that the region responsible for the abnormality is within a 7.3-Mb region between positions 104.2 and 111.5 Mb in 13q33.1q34. Located in 13q33.3, the EFNB2 gene has been suggested as a candidate to play a role in male urogenital abnormalities in several studies [Dravis et al, 2004;Garcia et al, 2006;Walczak-Sztulpa et al, 2008;Kirchhoff et al, 2009;Andresen et al, 2010;Wang et al, 2017]. In fact, EFNB2 haploinsufficiency may provide a causative explanation for the observed urogenital abnormalities in our 13q deletion male patients 2 and 3.…”
Section: Urogenital Abnormalitiesmentioning
confidence: 53%
“…In fact, EFNB2 haploinsufficiency may provide a causative explanation for the observed urogenital abnormalities in our 13q deletion male patients 2 and 3. Wang et al [2017] suggested the EDNRB gene, located in the 13q22.3 region, as another candidate for urogenital abnormalities. Although both our female patients carry deletions involving EDNRB , only patient 5 presents external genital hypoplasia, suggesting that this correlation is not so definitive.…”
Section: Urogenital Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Eph/ephrin signaling plays an essential role in the maintenance of several biological processes, including synaptic plasticity, angiogenesis and vasculogenesis and stem cell differentiation . EFNB2 haploinsufficiency had been involved in few human pathologies such as urogenital or anorectal anomalies …”
Section: Discussionmentioning
confidence: 99%
“…In human pathology, EFNB2 haploinsufficiency is involved in urogenital or anorectal anomalies and is suspected to be implicated in CHD or in congenital eye malformation . Few patients with partial deletions of the long arm of chromosome 13 have been reported .…”
Section: Introductionmentioning
confidence: 99%